'Ordre et beauté': Jonathan Harvey's musical responses to Baudelaire. Issue 3 (1st December 2021) - Downes, Michael
Abstract : The British composer Jonathan Harvey is generally associated with Eastern sacred texts rather than the secular Western literary canon. However, evidence from works composed over several decades suggests that Charles Baudelaire was a significant if subterranean influence upon his music. This article considers these works in detail. 'L'Horloge' ['The Clock'] (1963) is a remarkable interpretation of Baudelaire's text which reveals in it parallels with Harvey's own contemporary preoccupations with the nature of musical time. Correspondances (1975) is a sequence of settings from Les Fleurs du mal and interludes and 'fragments' for piano which may be arranged in numerous orders at the discretion of the performers. Finally, the instrumental works Hidden Voice (1996) and Hidden Voice II (1999) demonstrate that the poet's ideas remained an inspiration to Harvey well into his compositional maturity. Particularly striking is the variety and originality of these musical responses. Baudelaire's real significance for Harvey was perhaps as an exemplar of aesthetic ideals – of 'order and beauty' – rather than merely as a source of musically suggestive images and phrases.